PTU-091 Multimatrix mesalazine in paediatric ulcerative colitis: a pharmacokinetic and safety study. (22nd June 2015) - Cuffari, C; Pierce, D; Korczowski, B; Fyderek, K; Van Heusen, H; Hossack, S; Martin, P
Abstract : Introduction: Data on mesalazine (5-aminosalicylic acid; 5-ASA) use in cases of paediatric ulcerative colitis (UC) are limited. In this phase 1, randomised, open-label, multicentre study (NCT01130844 ), pharmacokinetic (PK) and safety profiles of 5-ASA and metabolite acetyl-5-ASA (Ac-5-ASA) were examined in youth with UC diagnoses after once-daily (QD) multimatrix mesalazine administration. Method: Upon enrolment, patients (pts; aged 5–17 y with diagnosis of UC ≥3 mo, stratified by body weight) were given 30, 60, or 100 mg/kg multimatrix mesalazine QD for 1 wk. The existing, approved, 1200 mg tablet was supplemented with newly developed, smaller-sized 300 and 600 mg multimatrix mesalazine tablets in order to achieve the appropriate study doses in children. Mesalazine was administered at home (Days 1–4) and at the clinic (Days 5–7); onsite, safety evaluations were performed, and blood and urine samples obtained for PK analyses. A validated LC/MS/MS assay was used to determine plasma and urine concentrations of 5-ASA and Ac-5-ASA. Key PK parameters assessed included maximum concentration (Cmax, ss ), time of Cmax, ss (tmax ), area under the curve for 1 dose interval (AUCss ), renal clearance (CLR ), and% dose absorbed. Results: In total, 52 pts (21, 22, and 9 pts at 30, 60, and 100 mg/kg, respectively) were randomised and treated. Mean (standard deviation) age was 13.3 (3.1) y, and median (range) time since UC diagnosis was 1.8 (0.2–9.6) y. By Day 5, 5-ASA and Ac-5-ASA plasma concentrations reached steady state for all dose groups. On Day 7, for both 5-ASA and Ac-5-ASA, mean Cmax, ss and AUCss showed dose proportional increases from 30 to 60 mg/kg cohorts. Mean% 5-ASA absorbed for 30, 60, and 100 mg/kg doses were 29.4%, 27.0%, and 22.1%, respectively. Mean CLR ranges were 5.0–6.5 L/h for 5-ASA and 10.0–16.2 L/h for Ac-5-ASA. Treatment-emergent adverse events (TEAEs) were reported by 19.2% of pts; no new safety signals were identified. Events were similar among age and dose groups, and no TEAEs led to premature discontinuation. Conclusion: The PK profiles of 5-ASA and Ac-5-ASA in children and adolescents with UC receiving multimatrix mesalazine across all dose levels were similar to those from historical adult data with respect to absorption, clearance, and intersubject variability. Overall, multimatrix mesalazine was well tolerated with no new safety concerns identified. Disclosure of interest: C. Cuffari Consultant for: Shire, Prometheus, Abbott Nutrition, D. Pierce Shareholder of: Shire, GlaxoSmithKline, Employee of: Former employee of Shire, B. Korczowski Grant/Research Support from: Shire, K. Fyderek Grant/ Research Support from: Shire, H. Van Heusen Shareholder of: Shire, Employee of: Shire, S. Hossack Employee of: Covance, which received funding from Shire, P. Martin Shareholder of: Shire, Employee of: Shire.